(untitled) (Journal of Medicine, 2014)
The Middle East respiratory syndrome coronavirus (MERS-CoV) is a novel coronavirus (nCoV) first reported on 24 September 2012 on ProMED-mail by Egyptian virologist Dr. Ali Mohamed Zaki in Jeddah, Saudi Arabia. He isolated and identified a previously unknown coronavirus from the lungs of a 60-year-old male patient with acute pneumonia and acute renal failure. MERS-CoV is the sixth new type of coronavirus like SARS (but still distinct from it and from the common-cold coronavirus). Until 23 May 2013, MERS-CoV had frequently been referred to as a SARS-like virus, or simply the novel coronavirus, and colloquially on messageboards as Saudi SARS. These respiratory viruses are an emerging threat to global health security and have led to worldwide epidemics with substantial morbidity, mortality, and economic consequences. Currently confirmatory testing requires molecular diagnostics including either a positive PCR on at least two specific genomic targets or a single positive target with sequencing on a second. However, the interim recommendations for laboratory testing for MERS-CoV should be consulted for the most recent standard for laboratory confirmation. Hajj and Umrah draws some of the largest crowds in the world, and the large crowds bring some health and safety risks. The virus can spread from person to person when people are touching or very near each other, so pilgrims in crowds may be at risk. Symptoms of MERS include fever, cough, and shortness of breath. Most people infected with MERS have had severe illness and pneumonia, and about half of them have died. If anyone develops a fever and cough or difficulty in breathing within 14 days after returning from trip, must seek medical care. The Embassy of Saudi Arabia recommends that the following groups should postpone their plans for Hajj and Umrah in 2013: the elderly, the terminally ill, pregnant women, and children. DOI: http://dx.doi.org/10.3329/jom.v14i2.19634 J Medicine 2013, 14(2): 156-163